PROBLEMS OF INTEGRATION AND COOPERATION OF CENTRAL ASIAN COUNTRIES IN TIME OF GEOPOLITICAL UNCERTAINTY - Duisen, Г.М.; Aitzhanova, Д.А.; Zhuzbayeva, У.Д. (Journal of Oriental Studies, 2024)
The authors highlight the features and differences in the development of the countries of the region, their common economic and political interests, emerging on the basis of modern geopolitical uncertainty and tension. The need for government reforms and the development of current areas of foreign policy cooperation between Kazakhstan and Central Asian countries is substantiated. The main provisions of the study are necessary for building a region-wide joint policy for the life support of the countries of the Central Asian space and maintaining stability and sustainability in the format of dynamic changes in world development. Today, Central Asia (the center of the Asian macroregion, economically, politically and resource-rich) represents a geographical place of intersection of interests and special attention of the leading actors of the world community and international structures. At the same time, the uniqueness of Kazakhstan's position lies in the fact that the country is located at the crossroads of many transport links and is of great strategic importance in identifying key tracks of economic development and ensuring the security of Central Asian states. There is a significant potential for cooperation to expand the trade potential between the Central Asian countries. Key words: challenges, Central Asia, Kazakhstan, systemic problems, cooperation, Central Asian region.